Conditions and a computation method of the constrained regulation problem for a class of fractional-order nonlinear continuous-time systems - Si, Xindong; Yang, Hongli; Ivanov, Ivan G. (Zielona Góra: Uniwersytet Zielonogórski)
The constrained regulation problem (CRP) for fractional-order nonlinear continuous-time systems is investigated. New existence conditions of a linear feedback control law for a class of fractional-order nonlinear continuous-time systems under constraints are proposed. A computation method for solving the CRP for fractional-order nonlinear systems is also presented.
Keywords: fractional-order nonlinear systems; constrained regulation; positively invariant set; linear programming